Antibiogram of Extended Spectrum Beta-Lactamase and AmpC Beta- Lactamase Producing Escherichia coli among the Patients Attending a Selected Tertiary Health Care Hospital - Rahman, Lotifur; SMZH, Asna; Aziz, Md Abdul (Journal of Enam Medical College, 2022)
Background: The global emergence and spread of Extended Spectrum Beta-Lactamases (ESBLs) and AmpC beta-lactamases (AmpC) producing Escherichia coli (E. coli) have become a global concern because of inducing resistance toward most of the antimicrobial classes and making the treatment difficult. Hence, this study was aimed to assess the prevalence and antibiotic resistance pattern of ESBL and AmpC beta-lactamases producing E. coli in Bangladesh Institute of Health Sciences (BIHS) General Hospital. Objectives: To assess the prevalence of ESBL +ve and AmpC +ve producing E. coli and to see their antibiotic resistance pattern in BIHS General Hospital. Materials and Methods: A total of 675 samples were subjected to aerobic bacteriologic culture in the department of Microbiology, BIHS General Hospital, Mirpur, Dhaka, during the period of 1st July 2016 to 30th June 2017. Specimens were collected from hospitalized and outdoor patients of different age and sex groups. All the isolates were identified by standard microbiological technique and their antibiotic susceptibility was observed by disk diffusion method. Strict aseptic precautions were taken all through the culture system. Results: Out of 675 specimens, 150 (22.22%) culture yielded growth of E. coli. Among them 47 (31.3%) were ESBL +ve, 27 (18%) were AmpC +ve and 7 (4.7%) were both AmpC +ve and ESBL +ve E. coli. Conclusion: Advance antibiotic resistance surveillance is necessary to guide the appropriate and judicious antibiotic use. The antibiotic should be used after performing culture and sensitivity test to minimize increasing trend of drug resistance. J Enam Med Col 2020; 10(3): 179-185